Parental Refusal of Childhood Vaccines and Medical Neglect Laws - Parasidis, Efthimios (Am J Public Health, 2017)
Objectives. To examine the relation of vaccine refusal and medical neglect under child welfare laws. Methods. We used the Westlaw legal database to search court opinions from 1905 to 2016 and identified cases in which vaccine refusal was the sole or a primary reason in a neglect proceeding. We also delineated if religious or philosophical exemptions from required school immunizations were available at the time of adjudication. Results. Our search yielded 9 cases from 5 states. Most courts (7 of 9) considered vaccine refusal to constitute neglect. In the 4 cases decided in jurisdictions that permitted religious exemptions, courts either found that vaccine refusal did not constitute neglect or considered it neglect only in the absence of a sincere religious objection to vaccination. Conclusions. Some states have a legal precedent for considering parental vaccine refusal as medical neglect, but this is based on a small number of cases. Each state should clarify whether, under its laws, vaccine refusal constitutes medical neglect.